MORPHOMETRIC AND MERISTIC ANALYSIS OF ASIAN KNIFEFISH (Notopterus notopterus) IN SAIL RIVER, PEKANBARU RIAU PROVINCE - Isma Mulyani; Budijono Budijono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
This study was conducted from January-April 2017 located in Sail River, Pekanbaru City, Riau Province. The aim of this study was to investigate morphometric and meristic characters of Asian knifefish (Notopterus notopterus) besides as the most accurate initial identification of certain species. Fish samples were collected using sero (traditional setnet) to be further observed for their morphometric and meristic characters using ruler of 50 cm. Morphometric analysis applied to the Asian knifefish resulted in 23 characteristics. The highest value was found in the total length (TL) of female fish which reached 135-270 mm, while the lowest was in the characteristic of snout length (SNL) in male fish of 1,3-1,8 mm. A total of 8 meristic characteristics were observed, included: Dorsal fin rays (D), Pectoral fin rays (P), Ventral fin rays (V), Anal fin rays (A), Scales before dorsal fins, Circumference scales, Scales at caudal peduncle, and Scales along lateral line. According to its morphological characters, Asian knifefish has a flat body with sideways-elongated oval shaped and a humpback appearance. The shape of head near the back is relatively straight and scaly. The mouth of this species has protractile structure (able to protrude) with a terminal position and no tentacles. Asian knifefish has a large size of mouth opening as they are carnivorous fish. Adult fish has an evenly brown color, slightly concave dorsal shape, dark bands all over the body; and white-silver head color with enormous small gray spots. The fish body is covered with cycloid scales.